EDUCATION AND SUBJECTIVE WELL-BEING IN THE CONTEXT OF ASSESSMENT OF QUALITY OF ADULTS LIFE - Stiegele, Dace; Paipare, Mirdza (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
In recent decades, quality of life issues and research have been increasingly focused on seeing a direct link between indicators of subjective well-being and economic growth. In Latvia, the issue of subjective well-being has also been raised in recent years in population surveys, but there are no trends in emphasizing the importance of these indicators in the context of quality of life.In Latvia, education is included in the statistical data collection among the most important quality of life indicators. In Latvia, the level of life satisfaction decreases most rapidly at the age of 45-54.Purpose of the article: to research the components of quality of life in Europe and Latvia, identify significant indicators for the mantaining of adult quality of life and view on education and subjective well-being in the context of assessment of quality of adults life.Method: the study carried out an content analysis of the data of Eurostat population quality of life surveys, the EU and the Republic of Latvia's official guidelines on quality of life and lifelong learning, as well as pedagogical and psychological literature and scientific articles on quality of life, subjective well-being and adult education issues. Results: according to survey data, adults with higher level of education experience higher level of participation in lifelong learning activities; the level of education affects the assessment of life satisfaction.